Hubungan Karakteristik Responden, Pengetahuan Dan Luas Ventilasi Dengan Kejadian Skabies Pada Santri Pondok Pesantren X Semarang - Ana Novia Rahmawati; Retno Hestiningsih; Moh. Arie Wurjanto; Martini (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2021)
Background: Scabies is a contagious skin disease caused by Sarcoptes scabiei. Scabies is still a neglected health problem in the world. In Indonesia, scabies ranks 3rd out of 12 of the most common skin diseases. Islamic boarding school students are generally prone to scabies because they live and sleep in the same place. Scabies can be caused by gender, level of education lack of knowledge and the extent of inadequate ventilation. Objectives: This study aims to analyze the relationship between gender, knowledge and extent of ventilation with the incidence of scabies at the Nurus Sunnah Islamic Boarding School Semarang. Research Metodes: This study is a quantitative study with an observational analytic approach and a cross-sectional study design. The sample in this study were 107 respondents with a purposive sampling technique. Data collection using google form and analyzed using chi square. Results: The results of this study indicate that there are 19.6% of respondents suffering from scabies. There was a sex relationship with the incidence of scabies (p-value = 0.001), there was no relationship between the level of education and the incidence of scabies (p-value = 0.557), there was a relationship between the level of knowledge and the incidence of scabies (p-value = 0.036), there was a relationship between the extent of ventilation. with the incidence of scabies (p-value = 0.023). Conclusion: There is a relationship between gender, knowledge and extent of ventilation with the incidence of scabies in students of the Nurus Sunnah Islamic Boarding School in Semarang in 2020.